(untitled) (Revista Rupturas, 2022)
This article studies the political demonstration called I educate my children, held in San José, Costa Rica, in 2017. This social protest is a sample of the different expressions of political conservatism in opposition to sexual education policies, in charge of the Ministry of Public Education (MEP) of the Government of Costa Rica. At the same time, this demonstration gives an account of the discussions that took place during the 2017-2018 electoral campaign. The article studies the context and the main characteristics of this demonstration.